FACTORS INFLUENCING THE SUCCESS OF PERFORMANCE MEASUREMENT: EVIDENCE FROM LOCAL GOVERNMENT - Primarisanti, Herlina; Akbar, Rusdi (Journal of Indonesian Economy and Business, 2015)
There were only a few government institutions in Indonesia capable of preparing good accountability reports. Based on the survey conducted in the Special District of Yogyakarta, the study aimed to empirically examine the influencing factors in the development of the measure-ment system of performance, performance accountability and the use of performance informa-tion. Additionally, it also tried to interpret and to explain empirical evidence in the perspective of the institutional theory. The institutional theory was used to find out the extent to which the development of the measurement system of the performance, the performance accountability and the use of the performance information was influenced because of the presence of coercive, mimetic and normative isomorphism phenomena. The study used mixed methods that combined quantitative and qualitative study approaches simultaneously and a sequential explanatory strategy. It used Partial Least Square (PLS) analysis to test the hypotheses. It gave evidence that training, incentives and authority in decision making had significant impacts on the development of the measurement of the performance, the performance accountability and the use of the performance information. It contributed to the understanding of the influencing factors of the development of the measurement system of the performance, the performance accountability and the use of the performance information in order to improve the measurement system of the performance of government institutions.Keywords: performance measurement system, performance accountability, the used of performance information and mixed methods.